SEKOLAH ONLINE DI MASA PANDEMI COVID-19, BAGAIMANA TANGGAPAN GURU DAN SISWA SEKOLAH DASAR? - Nasikhin Nasikhin; Ikhrom Ikhrom; Agus Sutiyono (LPPM Universitas Muhammadiyah Muara Bungo, 2022)
This study aims to determine the learning experiences experienced by elementary school students and the efforts of teachers in tackling online learning problems during the Covid-19 pandemic. The sample in this study were eleven resource persons consisting of teachers and students. By using a qualitative approach and an exploratory case study conducted at SD N Sangubanyu 02, it was obtained research data that students' experiences in participating in online learning can lead to boredom, decreased seriousness and learning participation, low learning motivation, and not achieving intellectual satisfaction. Meanwhile, the handling efforts made by the teacher in tackling this problem are by maximizing the use of learning technology tools, modifying certain learning methods such as Project Based Learning, Integrated Curriculum, and Blended Learning. This study contributes to research on pedagogy and online learning by clarifying what the teacher's role is in finding problem solving for students' problems. Keywords : Learning Innovation, Online Learning, Digital Learning